Reconstruction of Regulation of the Authority to Address Determination of Village Head Election Results as the Object of State Administrative Object of State Administrative Disputes Based on Justice Value - Bernat Panjaitan; Anis Mashdurohatun; Sri Kusriyah (Journal of Social Research, 2023)
The State of Indonesia is a State of Law". As a constitutional state, Indonesia places the foundations of law above all else. The purpose of this study is to analyze and find regulations adjudicating the determination of village head election results as objects of dispute. State administration is not based on the value of justice. The results of the Election of the Village Head as the object of a state administrative dispute based on the value of justice. The paradigm in this study is Constructivism. The legal research used in this dissertation is qualitative legal research, i.e. non-doctrinal legal research using a socio legal research approach, and the nature of this dissertation research is descriptive. The theory used is Pancasila justice theory, dignified justice theory (Grand Theory), legal system theory (Middle Theory), as well as progressive legal theory and authority theory (Applied Theory). The results of the study found that the Reconstruction of regulations on the authority to adjudicate the Determination of Village Head Election Results as Objects of State Administrative Disputes based on the value of justice, Reconstruction of regulations on objects of state administrative disputes on Bodies or Officials and State Administrative Decisions as follows: contents of Law No. 51 of 2009 concerning the Second Amendment to Law No. 6 of 1986 concerning State Administrative Courts Paragraph (1) Number 8 concerning the meaning of State Administrative Agencies or Officials Paragraph (1) Number 9 concerning State Administrative Decisions Prior to reconstruction in the event of disputes over the determination of the Village head election committee regarding the results of the village head election not being resolved by the Regent can be directly challenged to the state administrative court.